A Prospective Study Using Propensity Score Matching to Compare Long-term Survival Outcomes After Robotic-assisted, Laparoscopic, or Open Liver Resection for Patients With BCLC Stage 0-A Hepatocellular Carcinoma. Issue 1 (25th January 2023) - Zhu, Peng; Liao, Wei; Zhang, Wan-Guang; Chen, Lin; Shu, Chang; Zhang, Zhi-Wei; Huang, Zhi-Yong; Chen, Yi-Fa; Lau, Wan Yee; Zhang, Bi-Xiang; Chen, Xiao-Ping
Abstract : Objective: To compare the short- and long-term outcomes of robot-assisted (RALR), laparoscopic (LLR), or open liver resection (OLR) in the treatment of Barcelona Clinic Liver Cancer (BCLC) stage 0-A hepatocellular carcinoma (HCC). Summary Background Data: Following the Balliol IDEAL classification, long-term oncological outcomes can be used to evaluate the value of minimally invasive techniques in the treatment of HCC, and to assess whether they should become a standard practice. Methods: Data from prospective cohorts of patients with BCLC stage 0-A HCC who underwent curative liver resection using OLR, LLR, or RALR at Tongji Hospital were reviewed. The short-term and long-term oncological outcomes of these 3 different surgical approaches after adequate follow-up were compared using propensity score matching to reduce selection bias. Results: Of 369 patients included in this study (71, RALR; 141, LLR; and 157, OLR), 56 patients in each of the 3 groups were chosen for further comparison, after propensity score matching. In the minimally invasive group (RALR+LLR), both the operative time and duration of Pringle's maneuver were significantly longer than those in the OLR group; however, the length of hospital stay was significantly shorter. There were no significant differences in the other intraoperative parameters and the incidence of postoperative complications among the 3 groups. HCC recurrence in the minimally invasive group when compared with the OLR group was characterized by a significantly higher proportion of single lesion or early-stage HCC. However, there were no significant differences in the 5-year disease-free survival (63.8%, 54.4%, and 50.6%) or overall survival rates (80.8%, 78.6%, and 75.7%, respectively) among the 3 groups. Clinically significant portal hypertension was the only risk factor that negatively affected the 5-year disease-free survival rate. Multivariate Cox regression analysis showed that clinically significant portal hypertension, serum alpha-fetoprotein level (≥400 ng/mL), and Edmondson-Steiner grading (III+IV) were independent risk factors for poor long-term survival. Conclusion: Both robotic and laparoscopic hepatectomies were safe and effective for patients with BCLC stage 0-A HCC when compared with open hepatectomy.